Extracellular Vesicles: Schistosomal Long-Range Precise Weapon to Manipulate the Immune Response - Avni, Dror; Avni, Orly (Frontiers in Cellular and Infection Microbiology, 2021)
Schistosomiasis (Bilharziasis), a neglected tropical disease that affects more than 240 million people around the world, is caused by infection with the helminth parasite Schistosoma. As part of their secretome, schistosomes release extracellular vesicles (EVs) that modulate the host immune response. The EV-harbored miRNAs upregulate the innate immune response of the M1 pathway and downregulate the differentiation toward the adaptive Th2 immunity. A schistosomal egg-derived miRNA increases the percentage of regulatory T cells. This schistosomal-inducible immunoediting process generates ultimately a parasitic friendly environment that is applied carefully as restrained Th2 response is crucial for the host survival and successful excretion of the eggs. Evidence indicates a selective targeting of schistosomal EVs, however, the underlying mechanisms are unclear yet. The effects of the schistosomes on the host immune system is in accordance with the hygiene hypothesis, attributing the dramatic increase in recent decades in allergy and other diseases associated with imbalanced immune response, to the reduced exposure to infectious agents that co-evolved with humans during evolution. Deciphering the bioactive cargo, function, and selective targeting of the parasite-secreted EVs may facilitate the development of novel tools for diagnostics and delivered therapy to schistosomiasis, as well as to immune-associated disorders.